Vocational and Higher Education: The Role of Trust in the Formation of Educational and Professional Trajectory - I. S. Kuznetsov (Moscow Polytechnic University, 2024)
The article compares the impact of student trust on their educational and career trajectories in vocational and higher education. Since 2015, in Russia, enrollment in upper-grade vocational education programs has exceeded enrollment in higher education programs, and increasingly, young people choose TVET (Technical and Vocational Education and Training) institutions. Therefore, interest in studying various factors influencing the specific trajectories in TVET and higher education is growing. One of these factors is trust, which remains insufficiently studied. Trust has a positive effect on various aspects of education (academic achievements, satisfaction, loyalty to the university, etc.), which can directly or indirectly determine the choice of further educational and professional trajectory. The research data comes from a survey of Russian TVET and higher education students. Particularly in higher education, in contrast to TVET, student trust (in other students, teachers and management) influences their plans regarding educational and career trajectories after graduation. However, this influence depends on the subject of trust and on the intended life trajectory.